Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2022)
The current issue of Studies in Second Language Learning and Teaching includes six papers, the first two of which offer syntheses of existing research and the remaining four are reports of original empirical investigations.